2011
DOI: 10.1590/s1516-635x2011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifier in broiler diets containing different fat sources

Abstract: This present study aimed at evaluating the effect of the addition of an emulsifier to diets containing soybean oil, poultry fat or their blend, on the performance, carcass traits, serum lipid levels, pancreatic lipase concentration and nutrient digestibility of broilers. A randomized block design was applied using a 3 x 2 factorial arrangement, with three fat sources (soybean oil, poultry fat, and a blend of 50% soybean oil and 50% poultry fat) and the addition or not of an emulsifier. In experiment I, broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 23 publications
11
25
0
Order By: Relevance
“…Therefore, the extra energy ingested by birds would be used to activate the mechanisms of heat loss and maintenance of body temperature, with no excess energy for the deposition as adipose tissue. However, our results are in agreement with those of Guerreiro Neto et al (2011) and Cho et al (2012), who did not verify an influence of the use of emulsifiers on the deposition of fat in the abdominal region of the birds.…”
Section: Concomitantsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the extra energy ingested by birds would be used to activate the mechanisms of heat loss and maintenance of body temperature, with no excess energy for the deposition as adipose tissue. However, our results are in agreement with those of Guerreiro Neto et al (2011) and Cho et al (2012), who did not verify an influence of the use of emulsifiers on the deposition of fat in the abdominal region of the birds.…”
Section: Concomitantsupporting
confidence: 90%
“…For these same characteristics, when the additives were used, Nagargoje et al (2016) did not observe variations in the relative weight of the cuts when comparing the groups of broilers fed diets containing lipase (10 000 IU kg -1 ) to the control group at the end of the period from 1 to 42 days. Guerreiro Neto et al (2011) also did not verify a variation in the carcass yield and cuts of the chickens that received rations supplemented with emulsifiers at 42 days of age.…”
Section: Concomitantmentioning
confidence: 89%
See 1 more Smart Citation
“…Total blood biochemical parameters were not affected by different inclusion rate of SO in present research, as observed by Fascina et al (2009) and Guerreiro et al (2011) who did not find any blood parameters differences between broilers fed vegetable oils. However, results of some studies do not agree with the findings of present experiment.…”
Section: Discussionsupporting
confidence: 70%
“…Bile salts in aqueous solution spontaneously aggregate to form micelles, these also mix with lipid products during digestion to form mixed micelles and enhance absorption (Stamp and Jenkins, 2008). Several studies have been conducted to investigate the effects of bile salt supplements and emulsifiers on broiler performance (Maisonnier et al, 2003;Al-Zawqari et al, 2010;Guerreiro et al, 2011). The addition of bile salts to poultry diets has resulted in an improvement of fat absorption in chicks (Kussaibati et al, 1982).…”
Section: Introductionmentioning
confidence: 99%